2013
DOI: 10.2478/s11756-013-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus UKMP-5M, an endogenous lipase producing actinomycete from Peninsular Malaysia

Abstract: Escalation in food industries unctuous wastes has led to serious anthropogenic problems to the environment. Parallel to "green strategy", growing awareness in biological treatment emphasizes efficacy of enzymatic technology for bioremediation. Pertinently, researchers are in search for new lipase-lipid interaction for improved outcome. Rhodococcus species have documented inadequate evidences on lipase enzyme production. Consequent assessments on Rhodococcus isolates from Peninsular Malaysia have identified twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…and Halomonas spp. are reported to produce lipase, , while based on a current study, Tetracladium genomes are enriched for esterase and pectate lyase domains . Lipase and esterase are important enzymes for PBSA degradation. , Furthermore, Tetracladium spp.…”
Section: Resultsmentioning
confidence: 81%
“…and Halomonas spp. are reported to produce lipase, , while based on a current study, Tetracladium genomes are enriched for esterase and pectate lyase domains . Lipase and esterase are important enzymes for PBSA degradation. , Furthermore, Tetracladium spp.…”
Section: Resultsmentioning
confidence: 81%
“…Tween 20 (Sigma-Aldrich) was an adequate sub strate for simple and fast detection of microbial lipolytic activity on agar plate. White-like precipitate appears around the colony having lipase activity (Nagarajan et al, 2014).…”
Section: Lipase Activity Assaysmentioning
confidence: 99%
“…Understanding the influence of variation in these factors is important to provide the optimal conditions that are essential for microbial metabolism in order to degrade the targeted pollutant in the environment [10]. A number of tropical bacteria have been identified with potential in the biodegradation of waste cooking oils, grease and kitchen waste [20]. Nzila et al [17] reported that a bacterial consortium (including Stenotrophomonas rhizophila, Sphingobacterium sp., Pseudomonas libanensis, P. poae and P. aeruginosa) isolated from wastewater in a Saudi Arabian city could degrade 90% of oil within 7-9 days.…”
Section: Introductionmentioning
confidence: 99%